A study of hepatoprotective effects of Curcuma Xanthorrhiza and Ipomoea Aquatica on thioacetamide-induced liver cirrhosis in rats / Salim Said Salim Alkiyumi - Salim Said, Salim Alkiyumi (2013)
In this work, an attempt was made to study the hepatoprotective effects of ethanol extracts of Curcuma xanthorrhiza and Ipomoea aquatica which are traditionally used for liver complications. The preliminary work involved an in vitro screening of free radical scavenging of both plants together with silymarin as an agent known to have prevention effect on cirrhosis. In order to study the hepatoprotective and possible mechanism of actions, thioacetamide was used to induce liver cirrhosis in rat model. For each plant extract experiment, 5 groups of rats were assigned as normal control, cirrhotic control, silymarin control, low dose and high dose plant extract. After two months of the experiment, the animals were sacrified and blood and tissues samples were collected for biochemical and histological studies. The parameters included serum liver biomarkers, ALP, AST, ALT, total protein, albumin and bilirubin; liver tissue histological examination; liver tissue Masson’s trichome staining and immunohistochemical staining of α-SMA; liver tissue antioxidant, CAT, SOD; liver tissue lipid peroxidation maker, MDA; serum proinflammatory and profibrotic cytokines TNF-α, TG-Fβ1; liver tissue NF-κB. Then, both plant extracts were subjected to fractionation using column chromatography and the obtained fractions were screened for hepatoprotective in thioacetamide-induced hepatotoxicity normal liver cell line (WRL-68). From each plant extract, the fraction which was most effective in WRL-68 was subjected to LCMS to identify the available compounds. From the LCMS results of the fractions which exhibited best hepatoprotective results, violaxanthin from Ipomoea aquatica and xanthorrhizol from Curcuma xanthorrhiza were selected for further study. The selection of these compounds was based on the available information from the previous studies which iii could be used to infer that these compounds may be the main contributor in the hepatoprotective activity of the fraction and plant extract as whole. The results demonstrated that ethanol crude extracts of Curcuma xanthorrhiza and Ipomoea aquatica possess hepatoprotective activities in vivo against thioacetamide-induced liver cirrhosis which was proven in biochemical and histopathological findings. In the in vitro screening, Curcuma xanthorrhiza showed higher free radical scavenging than silymarin, however, the free radical scavenging of Ipomoea aquatica was less than silymarin. Nevertheless, both plant extracts significantly increased antioxidant enzymes and reducing lipid peroxidation, which suggest that both plants exhibit hepatoprotective activity, at least in part, by improving endogenous antioxidant status. In addition to that, both extracts exhibited antinflammatory properties to which might have inhibited fibrosis progression through the down regulation of proinflammatory and profibrotic cytokines which lead to the decrease in HSC activation and therefore decreased ECM deposition. This was proven by liver tissue α-SMA and Masson’s trichome staining. The hepatoprotective activities of both plant crude extracts were confirmed in vitro against thioacetamide induced cell damage in WRL-68. Furthermore, separated fraction 5 from Curcuma xanthorrhiza and fraction 11 from Ipomoea aquatica exhibited the highest hepatoprotective activities against thioacetamide induced cell damage in WRL-68. Similar to the animal study, both crude extracts, their fractions and selected compounds improved antioxidant enzymes and inhibited lipid peroxidation. The selected compounds were more effective than their crude extracts in protecting cell damage and improving antioxidant status. In fact, violaxanthin was more effective than silymarin. These results suggest that both plant extracts are hepatoprotective and the possible mechanism of action is likely to be through improving endogenous antioxidant status, iv decreasing proinflammatory and profibrotic cytokines, to which xanthorrhizol and violaxanthin may be the main contributors.